Respostas
respondido por:
10
(b+3,b+17,b+59)
(b+17) = (b+59)
(b+3) (b+17)
(b+17)(b+17)=(b+3)(b+59)
b^2 + 34b + 289 = b^2 + 59b + 3b + 177
62b - 34b = 289 - 177
28b = 112
b = 4
(b+3, b+17, b+69)
( 4+3, 4+17, b+69 )
(7, 21, 63)
(b+17) = (b+59)
(b+3) (b+17)
(b+17)(b+17)=(b+3)(b+59)
b^2 + 34b + 289 = b^2 + 59b + 3b + 177
62b - 34b = 289 - 177
28b = 112
b = 4
(b+3, b+17, b+69)
( 4+3, 4+17, b+69 )
(7, 21, 63)
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás